New Chloramphenicol Derivatives with a Modified Dichloroacetyl Tail as Potential Antimicrobial Agents - Artemis Tsirogianni; Georgia G. Kournoutou; Anthony Bougas; Eleni Poulou-Sidiropoulou; George Dinos; Constantinos M. Athanassopoulos (MDPI AG, 2021)
To combat the dangerously increasing pathogenic resistance to antibiotics, we developed new pharmacophores by chemically modifying a known antibiotic, which remains to this day the most familiar and productive way for novel antibiotic development. We used as a starting material the chloramphenicol base, which is the free amine group counterpart of the known chloramphenicol molecule antibiotic upon removal of its dichloroacetyl tail. To this free amine group, we tethered alpha- and beta-amino acids, mainly glycine, lysine, histidine, ornithine and/or beta-alanine. Furthermore, we introduced additional modifications to the newly incorporated amine groups either with protecting groups triphenylmethyl- (Trt) and tert-butoxycarbonyl- (Boc) or with the dichloroacetic group found also in the chloramphenicol molecule. The antimicrobial activity of all compounds was tested both in vivo and in vitro, and according to the results, the bis-dichloroacetyl derivative of ornithine displayed the highest antimicrobial activity both in vivo and in vitro and seems to be a dynamic new pharmacophore with room for further modification and development.